Controle social no estado do Maranhão: perfil dos conselhos de saúde - HORA, Ana Carolina Alves da (2021)
The Health Councils instituted by Law no. 8,142/90, enables community participation in the management of the Unified Health System (SUS) and allows to recognize strategies for consolidating the Social Control implementation in SUS. It is also perceived gaps that demonstrate what structural and administrative conditions these councils have and whether they allow actions to happen as established by law. This aim of this research was to evaluate the composition of instances for social control in health from the Health Councils of the state of Maranhão. It is an evaluation research, whose unit of analysis was the municipal health councils registered in the Health Councils Monitoring System (SIACS). Of the 218 health councils in the state of Maranhão, only 147 were registered until December 2020, which became the universe of study in this research. The primary data collect was used, by electronic questionnaire prepared in Google Forms® and the secondary, characterized by the survey and extraction of information contained in the SIACS. A score classification composed of five dimensions was elaborated, with information regarding the qualification of these councils based on the current legislation. In all, 67.4% (p = 147) of the councils were eligible for study, showing that 32.6% (p = 71) are non-existent with regard to registration in the system; 53.74% (p = 79) do not have an internal regulation; 80.27% (p = 118) do not have any other standard or resolution; 41.82% (n = 23) of the councils do not have a system for receiving complaints; 64.58% (p = 93) do not have their own headquarters; as for the entities that make up the users' follow-up, 76.24% (p = 106) are made up of religious organizations. Considering the score, 31.97% of the evaluated councils are adequate (n = 47), 42.18% are partially adequate (n = 62) and 25.85% presented results of inadequacy (n = 38). There is a predominance of low representativeness, little renewal of members, domination by more organized groups and weakening of the struggle on other participatory fronts. It is concluded that, there are potential weaknesses in meeting the regulatory standards of health councils in Maranhão, thus impacting directly on the effective practice of Social Control in the State.